Using STEM-Based 3D-Multimedia to Improve Students' Critical Thinking Skills in Uniform Circular Motion - Faizuna Roudhotin Nurilma; Edi Supriana; Markus Diantoro (Universitas Muhammadiyah Makassar, 2023)
Students' low critical thinking skills are an obstacle in learning uniform circular motion. The aim of the study was to describe the effect of using STEM-based 3D-multimedia in improving the critical thinking skills of students from the northern coast of Java in uniform circular motion material. This research is a pre-experimental with a one-group pre-test post-test design. The research sample was 26 students of class X-IPA MA Hasyimiyah Bancar. The treatment of the samples was carried out by using STEM-based 3D-multimedia during four face-to-face lessons in class. The results show that the students' critical thinking skills improved by 56,1% after the implementation of the STEM-based 3D multimedia. This quantitative result is proven by critical thinking skills indicators that can be identified in the students' critical thinking skills test answers. Therefore, it can be concluded that the use of STEM-based 3D-multimedia enhanced the students' critical thinking skills in uniform circular motion quite significantly.